2007
DOI: 10.1017/s0007123407000373
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Compliance: Infringements and Delays in Transposing European Union Directives

Abstract: What impact does the negotiation stage prior to the adoption of international agreements have on the subsequent implementation stage? We address this question by examining the linkages between decision making on European Union directives and any subsequent infringements and delays in national transposition. We formulate a preference-based explanation of failures to comply, which focuses on states' incentives to deviate and the amount of discretion granted to states. This is compared with state-based explanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 3 publications
5
142
2
1
Order By: Relevance
“…Making claims on the evolution of compliance they present the number of the different stages initiated each year (Ehlermann 1987;Börzel 2003;Sverdrup 2004). Here the main conclusion is that when controlling for increases in legislation and EU enlargement, "non-compliance appears to be modest and has remained stable or even declined over time" (Börzel 2003: 215;Mendrinou 1996; similary Thomson et al 2007). Alternatively, they aggregate the frequency with which the different stages are reached into a country index (Beach 2005 But are these really findings on compliance proper?…”
Section: Official Statistics On Infringement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Making claims on the evolution of compliance they present the number of the different stages initiated each year (Ehlermann 1987;Börzel 2003;Sverdrup 2004). Here the main conclusion is that when controlling for increases in legislation and EU enlargement, "non-compliance appears to be modest and has remained stable or even declined over time" (Börzel 2003: 215;Mendrinou 1996; similary Thomson et al 2007). Alternatively, they aggregate the frequency with which the different stages are reached into a country index (Beach 2005 But are these really findings on compliance proper?…”
Section: Official Statistics On Infringement Proceduresmentioning
confidence: 99%
“…However, for her this is neither a sufficient reason to abstain from using it, nor does she critically discuss her findings in this light. Similarly Thomson et al argue that although infringements are admittedly "an indirect measure of compliance (…) it is appropriate to formulate and test explanations of variation in these official indicators (since, MH/GF) they can be examined over a relatively large number of cases, enabling generalizations" (Thomson et al 2007). However, the problem of potential biases, even (or especially) in large N studies is not addressed.…”
Section: Official Statistics On Infringement Proceduresmentioning
confidence: 99%
“…She states the following, ' […] [N]ational legislators are less likely to comply with a provision if their representatives in the Council objected to its content'. In line with this argument, Thomson et al (2007) observe negative influences on the number of infringement procedures resulting from a member state's opposition. They demonstrate that 'incentives to deviate', which is the distance between member states' preferred and actual outcome confirmed in the directive, correlate positively with the likelihood of infringements (see also Thomson 2010).…”
Section: Europeanisation and Implementationmentioning
confidence: 71%
“…He also examined differences among the average transposition records of countries in different worlds, and found only marginal differences. Similarly, Thomson et al (2007) and Thomson (2007) found little difference among the compliance records of countries in different worlds.…”
mentioning
confidence: 89%
“…Falkner et al's (2005) worlds of compliance have been the subject of debate in this journal and elsewhere (e.g. Toshkov 2007; Thomson et al 2007;Thomson 2007;Falkner et al 2007a;Falkner 2007). None of these studies focus specifically on the central proposition of the worlds of compliance typology outlined above: namely, that the effects of misfit and social partner influence differ by cultural context.…”
mentioning
confidence: 99%